Corrosion behavior of stainless steel weldments in physiological solutions. (3rd January 2018) - Farooq, A; Azam, M; Deen, K M
Abstract: In this study corrosion behavior of TIG welded 316L stainless steel plates in simulated biological solutions is investigated. The mechanical testing results showed slight decrease in ductility after welding and the fracture surface represented mixed cleavage and inclusions containing dimple structure. The heat affected and weld zone (WZ) demonstrated higher corrosion potential and relatively large pitting tendency than base metal (BM) in both Hank's and Ringer's solution. The formation of delta ( δ ) ferrite in the heat affected and WZ decreased the corrosion resistance as confirmed from potentiodynamic Tafel scans. The decrease in pitting resistance and lower protection tendency of the WZ compared to BM and heat affected zone was also quantified from the cyclic polarization trends.